2023
DOI: 10.3390/s23031188
|View full text |Cite
|
Sign up to set email alerts
|

Differential Sensing with Replicated Plasmonic Gratings Interrogated in the Optical Switch Configuration

Abstract: A new plasmonic configuration is proposed for application in a sensor and demonstrated for the detection of variations in the bulk refractive index of solutions. The configuration consists of monitoring two diffracted orders resulting from the interaction of a TM-polarized optical beam incident on a grating coupler, operating based on an effect termed the “optical switch”. The two monitored diffracted orders enable differential measurements which cancel the drift and perturbations common to both, leading to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
(30 reference statements)
0
9
0
Order By: Relevance
“…Then, in this configuration with 120 nm gold layer thickness, the sample is a refractive index sensor. Bruhier et al 7 found a detection limit on the refractive index of 2x10 -7 RIU, while E. Laffont et al 8 found a detection limit of 10 -6 RIU with their transducers in the switch configuration. Then, standards of 10 -6 RIU were fixed on our sample to validate their quality.…”
Section: Methodsmentioning
confidence: 98%
“…Then, in this configuration with 120 nm gold layer thickness, the sample is a refractive index sensor. Bruhier et al 7 found a detection limit on the refractive index of 2x10 -7 RIU, while E. Laffont et al 8 found a detection limit of 10 -6 RIU with their transducers in the switch configuration. Then, standards of 10 -6 RIU were fixed on our sample to validate their quality.…”
Section: Methodsmentioning
confidence: 98%
“…n i and k 0 respectively represent the RI of the sensing medium and the wavenumber of the incident beam. This figure is extracted from [149]. Reprinted with permission from https://doi.org/10.3390/s23031188.…”
Section: Résumémentioning
confidence: 99%
“…A DAQ (data acquisition) device (8) and a computer (9) were used to record the measurements. This figure is extracted from[149]. Reprinted with permission from https://doi.org/10.3390/s23031188.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This effect involves a transfer of energy between two orders diffracted by a deep sinusoidal metallic grating, as the angle of incidence is varied over a few degrees about a specific angle of incidence, where the power in both diffracted orders is equal. Sensing based on this effect was demonstrated for the first time by detecting small changes in the bulk refractive index of aqueous [23] and gaseous media [24] with very good performance (in the range of 10 −6 -10 −7 RIU) in terms of limit of detection (LOD). The main advantages of this configuration include the ability to perform differential measurements in real time using a simple interrogation setup and the ability to fabricate the grating couplers cost-effectively.…”
Section: Introductionmentioning
confidence: 99%